2015
DOI: 10.1088/1748-6041/10/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Sphere-shaped nano-hydroxyapatite/chitosan/gelatin 3D porous scaffolds increase proliferation and osteogenic differentiation of human induced pluripotent stem cells from gingival fibroblasts

Abstract: Hydroxyapatite (HA) is an important component of human bone and bone tissue engineering scaffolds. A plethora of bone tissue engineering scaffolds have been synthesized so far, including nano-HA/chitosan/gelatin (nHA/CG) scaffolds; and for seeding cells, stem cells, especially induced pluripotent stem cells (iPSCs), have been a promising cell source for bone tissue engineering recently. However, the influence of different HA nano-particle morphologies on the osteogenic differentiation of human iPSCs (hiPSCs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 48 publications
(67 reference statements)
0
46
0
1
Order By: Relevance
“…Its presence in scaffold, not only produces chemical stimuli which remarkably enhance the physical attachments of cells, but also creates surface roughness for further stimulation cell‐surface adhesion . It is interesting to note that the shape of the nHA, whether spherical or slender, has significant impact on proliferation and osteogenic differentiation of stem cells …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Its presence in scaffold, not only produces chemical stimuli which remarkably enhance the physical attachments of cells, but also creates surface roughness for further stimulation cell‐surface adhesion . It is interesting to note that the shape of the nHA, whether spherical or slender, has significant impact on proliferation and osteogenic differentiation of stem cells …”
Section: Discussionmentioning
confidence: 89%
“…6,8 It is interesting to note that the shape of the nHA, whether spherical or slender, has significant impact on proliferation and osteogenic differentiation of stem cells. 47 Besides chemical properties, as already mentioned, topography and pore structure are physical characteristics of the scaffold that can affect seeded cell activity. The technique that we employed in manufacturing the scaffold was freeze drying combined with particle leaching.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that topography can also affect the differentiation lineages of cells. Several lineages including chondrogenic differentiation, osteogenic differentiation, and neuronal differentiation have been studied [101][102][103].…”
Section: Stiffness Effectsmentioning
confidence: 99%
“…Notably, the sphere-shaped nano-HA in HA/CG scaffolds greatly improved the osteogenic differentiation of human iPSCs as compared to rod-shaped. Consequently, human iPSCs and sphere-shaped nano-HA/CG composites generated a significant amount of bone in vivo [121].…”
Section: Factors To Improve the Osteogenic Potential Of Ipscsmentioning
confidence: 99%